The sword of the lady - Stirling, S. M. (Stirling, S. M. Emberverse., 2010)
Rudi Mackenzie ventures to post-apocalyptic Nantucket, where he discovers a beautifully made sword waiting for him in the only house that remains standing, and taking possession of it, realizes that nothing will ever be the same.